Olympic and Paralympic coaches living with stress - is it such a problem? Potential implications for future coach education in sport - Loftus, S.; Taylor, R.; Grecic, D.; Harper, D. J. (International Sport Coaching Journal, 2023)
Following increased research into how situational and organizational stress affects coaches` performance and welfare, there is a need to understand how coaches appraise and cope with the stressors they experience. These experiences could help inform applied interventions that facilitate both positive behavioural and performance-related outcomes. This is particularly important in elite coaches who operate in international competitions. Thirteen Olympic coaches participated in semistructured interviews to identify how they appraised stress as they prepared for the Tokyo Olympic Games. The research identified nine subthemes, which were categorized into three general overarching themes: (a) stressors, (b) appraisal of stressors, and (c) coping mechanisms. Despite the prevalence of negative stressors, self-doubt, and self-presentational concerns, many coaches interviewed demonstrated a positive outlook in relation to stress. Furthermore, they had established strong communities of practice as coping mechanisms against the impact of stress on performance, welfare, and health. Therefore, this study provides novel insights into the broad range of physical, psychological, and emotional challenges faced by Olympic and Paralympic coaches in the buildup to Olympic and Paralympic Games. Coach education programmes can use this information to help coaches develop effective coping mechanisms, subsequently leading to more positive outcomes from the stressors they experience.